SPENDING THE FREE TIME OF STUDENTS PROFESSIONALLY, IMPROVING THEIR ENTREPRENEURIAL SKILLS AND PROVIDING SOCIAL SUPPORT TO THEM (Conferencea, 2022)
This article talks about the modern conditions and opportunities created for students to spend their free time productively, get an education, acquire a profession, improve entrepreneurship skills and provide them with social support.